The effect of circuit resistance training on improving the concentration of certain types of fat and body composition in women aged 25-30 years - Wafa, L.Dr. Riband Kamran Hama (Sulaimani Journal for Humanities, 2026)
The research included an introduction and its significance. The research problem stemmed from the fact that the majority of women attending training centers suffer from overweight and obesity, and most training programs rely solely on aerobic exercises under the pretext of burning the largest amount of fat and calories, or on repetitive exercises without utilizing mixed anaerobic and resistance training, such as circuit training. Therefore, the researcher decided to delve into this area by developing a training program using circuit resistance exercises to improve fat types and body composition in women. The research aimed to identify the effect of circuit resistance training on improving the concentration of certain fat types in women aged 25-30 years and the differences between the post-tests of the two groups. The research hypothesis was that there are statistically significant differences in improving the concentration of certain fat types and body composition between the post-tests of the two training groups. The research population and sample consisted of (16) female participants at the City Gym. The research included a presentation, analysis, and discussion of the results obtained by the researcher. The conclusions were that the training program developed by the researcher... It played a positive and active role in all variables (blood fat and body composition) in greater proportions than the control group, except for (muscle weight) in favor of the control group. As for the recommendations, relying on the repetitive method is not sufficient to reach the required weight, but rather it helps to build muscles more than other methods.
Keywords: Resistance training; circuit training